An investigation between the links of sustainable manufacturing practices and innovation - Litos, Lampros; Patsavellas, John; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Elsevier, 2023)
Without a clear sustainability agenda in place, manufacturing companies would typically aim for products with incremental improved performance for their customers or introducing novel and innovative products and services that appeal to their target audience. However, mounting pressures to improve environmental performance indicators (carbon emissions, waste) require companies to think about step change improvements in how they operate and manage energy and resources. Companies trying to make their products with less energy and materials (doing more with less) are likely to face, or must address, operational and systemic changes in order to achieve better outcomes for the environment or ESG targets. Part of the issue at hand is the complexity and effort required to design effective changes with positive environmental outcomes and minimal disruption for on-going operations and manufacturing performance. In this article the authors aim to extend and explore the utility of a novel maturity model for eco-efficiency into innovation processes and practices and better understand the implications for theory and practice.
Keywords: eco-efficiency; eco-effectiveness; sustainable manufacturing; practice maturity; improvement